The uniquely Singapore race : a promotional campaign for the "Uniquely Singapore" brand. - Tan, Venga Wenkai. (2008)
The Uniquely Singapore Race is a brand communications project for Singapore Tourism Board (STB) which aims to communicate the "Uniquely Singapore" brand to youths 18 to 26 years old in polytechnnics and universities of Singapore.